Responses of Different Types of Pulsating Aurora in Cosmic Noise Absorption. Issue 11 (11th June 2019) - Yang, Bing; Spanswick, Emma; Liang, Jun; Grono, Eric; Donovan, Eric
Abstract: A recent study (Grono & Donovan, 2018, https://doi.org/10.5194/angeo‐36‐891‐2018 ) reported two distinct categories of pulsating aurora: patchy pulsating aurora (PPA) and amorphous pulsating aurora (APA). In this study we compare the auroral intensity of five PPA events and seven APA events monitored by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) All‐Sky Imagers with co‐located cosmic noise absorption (CNA) from the Geospace Observatory wide‐beam riometers. Our results show significant correlations between CNA and the auroral intensity of the APA events but no correlation between CNA and the auroral intensity of the PPA events. Analysis of conjunctions with the electron flux data obtained from the FAST satellite, we found that electrons responsible for APA may extend to higher energy range than those for PPA. Plain Language Summary: A recent study reported two distinct categories of pulsating aurora, but the origin of the differences between these two types remains unknown. In this letter, a statistical survey has been carried out for the first time investigating responses of two types of pulsating aurora in cosmic noise absorption. The statistical result suggests that the electrons responsible for these two types of pulsating aurora have different energy ranges with one another, which has been further confirmed through in situ observations. Key Points: Amorphous pulsating aurora (APA) and patchy pulsating aurora (PPA) have different responses in cosmic noise absorption FAST observation suggests that electrons associated with APA have higher energy ranges than that with PPA